(untitled) (Comprehensive Journal of Science, 2026)
This study analyzes the role of social work in child welfare by clarifying children’s needs and problems and identifying the professional roles of social workers within care institutions. A descriptive-analytical approach was adopted. Children’s needs were classified into biological, cognitive, social, and emotional dimensions, while their problems were categorized as environmental and personal. The findings indicate that social work performs three main roles: preventive, therapeutic, and developmental. The study emphasizes strengthening professional programs and improving social workers’ competencies to enhance the quality of child welfare services.